A Hermeneutical Study of the Essentialities of Adult Peace Education - Hsiu-Chu Hsu (Adult Education Research Conference, 2007)
By including peace courses in graduate programs and essentializing criticality, nonviolence, and wholistic views, as represented by Paulo Freire, Mahatma Gandhi, and Thich Naht Hanh, respectively, adult education can promote a more peaceful society and include peace education as a subfield.